2017
DOI: 10.1371/journal.pone.0179991
|View full text |Cite
|
Sign up to set email alerts
|

Actinic keratosis modelling in mice: A translational study

Abstract: BackgroundActinic keratoses (AK) are pre-malignant cutaneous lesions caused by prolonged exposure to ultraviolet radiation. As AKs lesions are generally accepted to be the initial lesions in a disease continuum that progresses to squamous cell carcinoma (SCC), AK lesions have to be treated. They are also the second most common reason for visits to the dermatologist. Several treatments are available but their efficacy still needs to be improved. The UV-B-induced KA lesion mouse model is used in preclinical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The chronic UV exposure was incrementally increased from 90 to 180 mJ cm −2 s −1 , resulting in a gradual appearance of AK lesions that morphologically and histologically resembled actinic keratosis in humans (Fig. 1A and B) (44,45). Histological and preneoplastic characteristics of the AK lesions were confirmed by Haematoxylin/Eosin (H&E) staining (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic UV exposure was incrementally increased from 90 to 180 mJ cm −2 s −1 , resulting in a gradual appearance of AK lesions that morphologically and histologically resembled actinic keratosis in humans (Fig. 1A and B) (44,45). Histological and preneoplastic characteristics of the AK lesions were confirmed by Haematoxylin/Eosin (H&E) staining (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies published by several groups including our own have shown that AK can be modeled in mice using a prolonged UVB-exposure regimen, and that the morphology and histology of the lesions in mice resemble those in humans (44,45). Based on these observations, SKH-1 mice were subjected to a 20-week UVB-exposure regimen, as described in the methods section (44,48).…”
Section: Conventional or Painless Pdt Treatments Elicit Similar Lesion Clearance Responses In A Murine Model Of Actinic Keratosismentioning
confidence: 99%
“…Although this reconstructed human epidermis from UV-B-irradiated keratinocytes displayed a thinner stratum corneum compared to normal reconstructed human epidermis, a reactive epidermis to chronic UV-B irradiation, characterized by orthokeratotic hyperplasia with hypergranulosis and PCNA and PIPs overexpression, together with several patches of incidental AKs or in situ SCCs associated with hypogranulosis were the main features in our murine model of skin with CFC. These differences in the epidermal architecture can be explained if we consider that, similarly to other published murine models of AKs and NMSC [22,30,31], our model in SKH1 mice represents a better approach to the complexity of the skin with CFC than in vitro models, including reconstructed human epidermis.…”
Section: Discussionmentioning
confidence: 96%
“…Due to the proviral insertion of the murine leukemia virus at Hr locus, which leads to a recessive hypomorphic mutation, these mice do not develop fur but, contrary to nude mice, they are still immunocompetent [29]. According to Pillon et al, as most AKs and SCCs arise in elderly individuals who show structural differences in the skin with respect to younger individuals, SKH1 aged mice might be used to optimize their mouse model of AK [30]. Another reason to use SKH1 aged mice was because the skin barrier differs depending on age, showing an impairment in the elderly [13].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several treatment options available, but their efficacy still needs to be improved 3 . Basically, these treatments range from topical medications to light‐based therapies and procedures.…”
Section: Introductionmentioning
confidence: 99%